How Do I Narrate My Marriage: The Relationship Between Attachment Orientation and Quality of Autobiographical Memory - Yan Wang; Qianrong Wang; Dahua Wang; Brooke C. Feeney (Frontiers in Psychology, 2018)
Attachment orientations play important roles in the generation of emotional autobiographical memory (AM). However, little research has considered the quality of autographical narratives, which may reflect the structure and content of internal working models (IWMs) of attachment. The purpose of the current study was to investigate the relationship between attachment orientations and narrative quality of marriage-related autobiographical memories. Ninety-four married adults were asked to retrieve two episodes of emotional autobiographical memories. The coherence and vividness of their narratives were then coded. Results indicated that adults who were highly avoidant were more likely to present their memories in a less coherent way and to describe negative memories with more perceptual details. In contrast, attachment anxiety was associated with lower vividness of negative memories. The current findings suggest that an attachment schematic-processing strategy was used in narrating the attachment-related experiences.